EXPLORING THE PERSONALITY DEVELOPMENT OF THE MAIN CHARACTER IN 172 DAYS BY NADZIRA SHAFA: A PSYCHOLOGICAL ANALYSIS USING ERIKSON, FREUD, AND MASLOW - Herlina; Nurzin R. Kasau; Nurlaelah (Al-Hijr: Journal of Adulearn World, 2026)
This study aims to explore the personality development of the main character in 172 Days by Nadzira Shafa through the lens of psychological theory. Using a qualitative approach, the research applies psychological frameworks such as Erikson’s psychosocial development theory, Freud’s theory of personality, and Maslow’s hierarchy of needs to analyze the protagonist, Alya, as she navigates significant internal conflicts and undergoes emotional and behavioral transformations. Data were collected through Systematic Literature Review (SLR), following the PRISMA 2020 guidelines, which allowed for a comprehensive selection and analysis of relevant psychological and literary studies. The results show that Alya's journey from identity confusion to self-actualization is shaped by the dynamic interplay between societal expectations and her personal desires. This study contributes to the field of literary psychology by demonstrating how psychological theories can be effectively applied to literary character analysis, offering insights into the psychological development of characters in literature. The findings have implications for the broader understanding of character development in literary studies and provide a framework for analyzing complex psychological narratives in fiction.